Anticoagulation in Patients With Device-Detected Atrial Fibrillation With and Without a Prior Stroke or Transient Ischemic Attack: The NOAH-AFNET 6 Trial - Diener, Hans Christoph; Becher, Nina; Sehner, Susanne; Toennis, Tobias; Bertaglia, Emanuele; Blomstrom-Lundqvist, Carina; Brandes, Axel; Beuger, Vincent; Calvert, Melanie; Camm, A John; Chlouverakis, Gregory; Dan, Gheorghe-Andrei; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: Short and rare episodes of atrial fibrillation (AF) are commonly detected using implanted devices (device-detected AF) in patients with prior stroke or transient ischemic attack (TIA). The effectiveness and safety of oral anticoagulation in patients with prior stroke or TIA and device-detected AF but with no ECG-documented AF is unclear. METHODS AND RESULTS: This prespecified analysis of the NOAH-AFNET 6 (Non-Vitamin K Antagonist Oral Anticoagulants in Patients With Atrial High Rate Episodes) trial with post hoc elements assessed the effect of oral anticoagulation in patients with device-detected AF with and without a prior stroke or TIA in the randomized, double-blind, double-dummy NOAH-AFNET 6 trial. Outcomes were stroke, systemic embolism, and cardiovascular death (primary outcome) and major bleeding and death (safety outcome). A prior stroke or TIA was found in 253 patients with device-detected AF randomized in the NOAH-AFNET 6 (mean age, 78 years; 36.4% women). There was no treatment interaction with prior stroke or TIA for any of the primary and secondary time-to-event outcomes. In patients with a prior stroke or TIA, 14 out of 122 patients experienced a primary outcome event with anticoagulation (5.7% per patient-year). Without anticoagulation, there were 16 out of 131 patients with an event (6.3% per patient-year). The rate of stroke was lower than expected (anticoagulation: 4 out of 122 [1.6% per patient-year]; no anticoagulation: 6 out of 131 [2.3% per patient-year]). Numerically, there were more major bleeding events with anticoagulation in patients with prior stroke or TIA (8 out of 122 patients) than without anticoagulation (2 out of 131 patients). CONCLUSIONS: Anticoagulation appears to have ambiguous effects in patients with device-detected AF and a prior stroke or TIA in this hypothesis-generating analysis of the NOAH-AFNET 6 in the absence of ECG-documented AF, partially due to a low rate of stroke without anticoagulation.
Keywords: kardiostimulátor; Hemorrhage; device‐detected atrial fibrillation; Humans; atrial fibrillation; tranzitorní ischemická ataka; Stroke; Double-Blind Method; NOAH‐AFNET 6; Female; Aged; recurrent stroke; Pacemaker, Artificial; výsledek terapie; senioři; lidé; dvojitá slepá metoda; Atrial Fibrillation; Administration, Oral; Ischemic Attack, Transient; časové faktory; cévní mozková příhoda; ženské pohlaví; CHA2DS2‐VASc score; Male; anticoagulation; Treatment Outcome; Aged, 80 and over; senioři nad 80 let; krvácení; aplikace orální; mužské pohlaví; antikoagulancia; Time Factors; Anticoagulants; fibrilace síní